Microsecretory Adenocarcinoma of Salivary Glands: An Expanded Series of 24 Cases - Bishop, Justin A.; Sajed, Dipti P.; Weinreb, Ilan; Dickson, Brendan C.; Bilodeau, Elizabeth A.; Agaimy, Abbas; Franchi, Alessandro; Khurram, Syed Ali; Da Forno, Philip; Robledo, Juliana; Kalmar, John R.; Aguirre, Sarah; et al. (Head and Neck Pathology, 2021)
Microsecretory adenocarcinoma (MSA) is a recently described salivary gland tumor with a characteristic histologic and immunophenotypic profile and recurrent MEF2C-SS18 fusions. Because only six cases of MSA have been published, its complete clinicopathologic spectrum is unclear, and its biologic behavior has not been documented. Here, we present an updated and expanded experience of 24 MSA cases. All cases of MSA were obtained from the authors' files. Immunohistochemistry for S100, SOX10, p63, p40, SMA, calponin, and mammaglobin was performed. Molecular analysis was performed by targeted RNA sequencing, SS18 break apart fluorescence in situ hybridization, and/or reverse transcriptase polymerase chain reaction for MEF2C-SS18 fusion. Clinical follow-up was obtained from medical records. A total of 24 MSA cases were collected, from 13 women and 11 men, ranging from 17 to 83 years (mean 49.5 years). The vast majority (23 of 24) arose in the oral cavity, with the palate (n = 14) and buccal mucosa (n = 6) as the most frequent subsites. Tumors showed consistent histologic features including: (1) microcystic tubules, (2) flattened intercalated duct-like cells, (3) monotonous oval hyperchromatic nuclei, (4) abundant basophilic luminal secretions, (5) fibromyxoid stroma, and (6) circumscribed borders with subtle infiltration. The tumors were very consistently positive for S100 (24 of 24), p63 (24 of 24), and SOX10 (14 of 14) and negative for p40 (0 of 21), calponin (0 of 12) and mammaglobin (0 of 16), while SMA (4 of 20) was variable. MEF2C-SS18 fusion was demonstrated in 21 of 24 cases; in the remaining 3 cases with insufficient RNA, SS18 break apart FISH was positive. Treatment information was available in 17 cases, all of which were managed with surgery only. In 14 cases with follow-up (1-216 months, mean 30), no cases recurred or metastasized. MSA is a distinct salivary gland neoplasm with remarkably consistent clinical, histologic, immunophenotypic, and genetic features that generally behaves in an indolent manner following surgery alone. These observations solidify MSA as a unique, low-grade salivary gland carcinoma that warrants inclusion in the next version of the WHO classification of head and neck tumors.
CRIS-Team WoS Importer:2021-05-28